Efficient Oral Dosage Forms For Nsaids: Formulation And Optimization Of Dispersible Tablets - Ramesh Gharal, Rutuja; Sunil Pol, Komal; P. Jatte, Kalleshvar; M. Desai, Madhuri; M. Shewale, Monali (Journal of Neonatal Surgery, 2025)
Recent lifestyle changes have necessitated the development of dosage forms suitable for various patient demographics, including pediatrics and geriatrics. This investigation delves into the potential of orally disintegrating tablets (ODTs) to address challenges encountered by patients with swallowing difficulties or non-compliance. ODTs, which rapidly disintegrate upon contact with saliva, present advantages in patient tolerance, compliance, and bioavailability over traditional oral dosage forms. Different manufacturing techniques, including lyophilization, molding, and compression, were assessed, with direct compression identified as the most viable method for producing structurally sound ODTs. Ibuprofen was selected as a model drug due to its widespread use and relatively low bioavailability in conventional dosage forms. Synthetic superdisintegrants were utilized to improve the bioavailability and stability of ibuprofen ODTs. The formulation development process entailed meticulous analysis, considering factors such as excipient selection, drug bioavailability, stability, and manufacturing efficiency. Emphasis was placed on continuous innovation in formulation research, extending to novel delivery methods like drone delivery. Furthermore, there is growing interest in leveraging the oral cavity for systemic drug delivery, particularly for patients with swallowing difficulties or those needing rapid drug effects. Sublingual drug delivery emerges as a promising alternative, particularly beneficial for individuals with dysphasia or other limitations. These advancements aim to enhance medication adherence and effectiveness across diverse patient populations.